Audit Committee Diligence and Gender Diversity as Catalysts for Scale Efficiency in Nigerian Manufacturing Firms - Aigienohuwa, Osarenren; Irowa-Omoregie, Osasogie (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study examined the impact of audit committee diligence and gender diversity on scale efficiency in Nigerian manufacturing firms. Audit committee diligence, measured by the frequency of meetings, reflects the committee's commitment to ensuring effective oversight and operational efficiency. Gender diversity introduces diverse perspectives that enhance decision-making processes. Using a panel research approach with data from 50 listed Nigerian manufacturing firms over the period 2012–2022, the study employed panel regression models to analyze the relationship between audit committee attributes and scale efficiency, measured by scale efficiency based on turnover and assets. The results showed that audit committee diligence positively and significantly influenced scale efficiency based on assets, highlighting the importance of frequent and focused meetings in driving operational efficiency. However, diligence had an insignificant relationship with scale efficiency based on turnover, suggesting that its immediate impact on revenue-related efficiency may be limited. Conversely, audit committee gender diversity exhibited an insignificant relationship with both measures of scale efficiency, implying that gender diversity alone may not directly influence scale efficiency in the Nigerian context. The findings contribute to the growing literature on corporate governance by providing empirical evidence from an emerging economy. The study highlights the need for strengthening audit committee practices through enhanced training and promoting an inclusive governance environment that leverages diverse perspectives for better decision-making.Keywords: Audit committee diligence, Gender diversity, Scale efficiency, Nigerian manufacturing firms.
Keywords: Audit Committee Diligence; Gender Diversity; Scale Efficiency; Nigerian Manufacturing Firms